Post-Genomics and Skin Inflammation - Daniela Braconi; Giulia Bernardini; Annalisa Santucci (Mediators of Inflammation)
Atopic dermatitis and psoriasis are two chronic skin inflammatory diseases that have so far received a greater attention within the scientific community through different post-genomic approaches; on the contrary, acne, which is undoubtedly one of the most common skin disorders involving inflammatory processes, seems to be still quite neglected under the post-genomic point of view. In this paper, we will review how post-genomic technologies have provided new fundamental tools for the analysis of these three conditions and we will cast light on their potential in addressing future research challenges.